Caregiving in Schizophrenia: The Role of Self-Efficacy in Shaping Resilience Among Family Caregivers - Mochammad Sadam Hilbram Afrizal; Yeni Fitria; Fitrio Deviantony; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Journal of Rural Community Nursing Practice, 2026)
Background: Caring for patients with schizophrenia is a significant challenge for caregivers. The responsibility of caring for patients with schizophrenia creates its own pressures and burdens for caregivers, requiring resilience to adapt to these challenges. In addition, self-efficacy is essential for caregivers to maintain confidence and a positive outlook regarding their ability to provide care. Purpose: This study aims to analyze the relationship between self-efficacy and resilience among caregivers of patients with schizophrenia in the Sumbersari District of Jember. Methods: This research uses a cross-sectional correlational design. The population includes 177 caregivers of schizophrenia patients in the Sumbersari District, Jember. A non-probability purposive sampling technique was used, resulting in a total of 123 respondents. The research instruments used were the General Self-Efficacy Scale (GSES) and the Connor-Davidson Resilience Scale (CD-RISC), and data were analyzed using Kendall’s Tau-C test. Results: Most caregivers had low self-efficacy (64, 52%) and moderate resilience (116, 94.3%). The analysis revealed a significant positive relationship between self-efficacy and resilience, with a weak strength (p = 0.001; r = 0.202). This indicates that higher self-efficacy is associated with greater resilience. Conclusions: Caregivers with high self-efficacy tend to be more confident, optimistic, and capable of handling stress while caring for patients with schizophrenia, thus demonstrating stronger resilience in fulfilling their roles. In contrast, caregivers with low self-efficacy may feel less capable of managing caregiving responsibilities, making them more susceptible to psychological stress. It is recommended that interventions prioritize enhancing caregivers’ self-efficacy, as this may improve resilience.